Video Animasi Berbasis Flipa Clip Sebagai Media Digital Pembelajaran Pendidikan Agama Islam di Sekolah Dasar - Dhona Nurpratiwi Rafik Ahmad; Azizah Ahmad; Rini Wulan Sari; Ani Nur Aeni (Departement of Mathematics Education, 2023)
This study explores the use of Flipa Clip-based learning animation videos as digital media in learning Islamic Religious Education in Elementary Schools, one of which is as an interactive learning medium in learning Islamic Religious Education (PAI) material Faith in Rasulullah SWT for Elementary Schools. student. This research was conducted using the Design and Development (D&D) approach, with a series of studies on the processes of analysis, design, development and implementation. Data were obtained through instruments in the form of field documentation and questionnaires or questionnaires which were distributed to Islamic religious education teachers in elementary schools and middle school students in elementary schools. Data processing is done quantitatively. The data shows that learning animation videos based on Flipa Clip as a digital media for PAI learning in elementary schools are very easy to convey learning because the video design is attractive and interactive where there are animated characters, there are songs about prophets and apostles in it. so that learning activities are more varied and attract student learning motivation. When watching the Flipa Clip-based learning animation video as a digital media for PAI learning in elementary school, most of the students felt happy.